Urine output in diagnosing acute kidney injury and predicting mortality - Md Ralib, Azrina; Mat Nor, Mohd Basri (2015)
Background: Urine output is the oldest biomarker of AKI. Clinically it can be the first indication of kidney dysfunction, especially in critical care settings where hourly urine outputs are routinely measured. It has been shown that the ideal urine output threshold for prediction of mortality or dialysis was 0.3 ml/kg/h for moving block of 6 hours.